An approach for preparing an absorbable porous film of silk fibroin-rice starch modified with trisodium trimetaphosphate - Racksanti,A. (John Wiley and Sons Inc., 2015)
© 2014 Wiley Periodicals, Inc. The absorbable porous material, especially gelatin porous film, is widely used for surgical use to stop bleeding, but its price is quite high. Thus, a new material at lower price with desirable properties is required. This article presents an approach to prepare a porous film of silk fibroin-rice starch (SF-RS) modified with trisodium trimetaphosphate (STMP). The preparation was performed using freeze-drying method aiming to increase the porosity and improve some other properties of the modified porous film. The solutions of SF and RS (5:95 weight ratio) and STMP were mixed and adjusted to pH 12 before being neutralized to pH 7 and freeze-dried for 48 h. Result from the SEM images showed that the average pore size of the SF-RS film increased from 17 to 126 μm after STMP was added up to 5.0% w/w. Similar to the SF-RS-STMP hydrogel, the linkages within the modified SF-RS porous film also occurred mainly between the O-H groups of RS and the triphosphate group of STMP. Moreover, cross-linking density of the porous film increased with the increasing content of STMP, evidenced from the increase of relative methylene blue adsorption. The addition of STMP also affected the physical properties of the modified porous film such as degree of swelling, oxygen permeability, but not the water solubility. Whereas, the residual ash of the modified porous films was lower than 2.0% and the degradation of the film ceased after soaking in 0.01M PBS solution for about 2 weeks.